AB0560 Evaluation of endothelial function in tocilizumab-treated rheumatoid arthritis patients refractory to TNF alfa inhibitors therapy. (23rd January 2014) - Covelli, M.; Notarnicola, A.; Lanciano, E.; Coladonato, L.; Rotondo, C.; Di Teo, C.; Locorotondo, M.; Mandurino, C.; Dachille, A.; Carbonara, R.; Ciccone, M.M.; Lapadula, G.
Abstract : Background: Cardiovascular disease is the major cause of excessive mortality in rheumatoid arthritis (RA). The endothelial dysfunction represents the earlier manifestation of Atherosclerosis and it predicts cardiovascular events. The effect of tumor necrosis factor alpha blockers and anti-CD20 (Rituximab) on endothelial function in RA patients has already been studied. It seems that both the anti-TNF alpha and Rituximab improved endothelial function after a 12-week treatment, even if the anti-TNF alpha effect is transient. The aim of the present study was to assess whether tocilizumab (anti-IL6) therapy affected the endothelial function in RA patients too. Objectives: To evaluate endothelial function in Tocilizumab treated rheumatoid arthritis refractory to tumor-necrosis-factor alpha inhibitor theraphy. Methods: Five consecutive RA patients (5 women; age range 38-51 years) without other cardiovascular risk factors were enrolled. These patients received intravenous tocilizumab every 28 days (mean of treatment 8, 8 months). Flow-mediated endothelium-dependent vasodilatation (FMD%) was measured at day 0 prior to the tocilizumab infusion and at week 12 (before the infusion) by brachial ultrasonography. Normal range of FMD% value is between 5% and 10%. Results: At week 12, FMD% values decreased in three out of five patients (mean ± SD 4, 83±3, 37%, range 2, 46 - 11, 89%); in one patient no FMD% values variation was found. On the contrary, in the other patient we observed an increase (range 3, 94 - 5.62). In two out of three patients the decreased FMD% value was a little higher than the lower limit of normal; in the other one, it was less than 5% (2, 46%). Conclusions: Our study demonstrates an active effect of tocilizumab on endothelial function in RA patients refractory to TNFalpha blockers. Further data needs to establish what kind of effect on endothelial function is mediated by tocilizumab. Disclosure of Interest: None Declared